The Negative Impact of "Mass Culture" on the Consciousness of the Youth of Uzbekistan - Miralieva Dilafruz Takhirovna; Yuldasheva Sharofat (Zien Journals, 2022)
This article reveals the methods and means of developing students' skills to combat "mass culture" through the heritage of our ancestors and the development of scientific and methodological recommendations for their use in the educational process.
Keywords: mass culture; globalization; harmonious personality; heritage of ancestors